Building administrative capacity under developmental states in Chile and Singapore: a comparative perspective. (June 2021) - Shamsul Haque, M.; Puppim de Oliveira, Jose A.
Administrative capacity depends on the nature of the state of which the administrative system is an integral part. In recent years, there has been a revival of debates on the role of public administration under developmental states in Southeast Asia and Latin America. A major analytical component of developmental states has been their administrative capacity and how to build it. There are significant variations in administrative capacity among developmental states caused by divergences in their historical, economic, political, and cultural contexts. This article compares two cross-continental cases (Singapore and Chile) with regard to the formations of developmental states shaping their administrative systems and capacity-building initiatives. It examines the divergences in their state formations and the contextual factors affecting their administrative capacity. The article concludes by making some generalizations, offering an analytical framework for further research, and suggesting policies needed for building effective administrative capacity. Points for practitioners: This article highlights the significance of administrative capacity-building for development. It explores how this capacity is shaped by the formation of the state under which public administration functions. In explaining this relationship between state formation and public administration, the article specifically focuses on the "developmental" state, compares two cross-continental cases (Singapore and Chile) as regards how these two developmental states differ and cause variations in their administrative systems, and explains the major contextual factors leading to such variations. This understanding is crucial to designing effective policies for building administrative capacity in any country depending on its state formation and context.